Micromechanical characterization and dynamic wear study of DC-Arc coated cemented carbide cutting tools for dry titanium turning. Issue 22 (15th November 2021) - Mishra, Sarvesh Kumar; Talwar, Dhruv; Singh, Kushaal; Chopra, Ankush; Ghosh, Sudarsan; Aravindan, Sivanandam
Abstract: The present study investigates the micromechanical properties of ceramic coated WC/Co tools and their influence on wear performance during dry Ti6Al4V turning. Physical and micromechanical characterization have been performed for the evaluation of the PVD coating properties. Higher hardness, elastic modulus, and adhesion strength have been obtained for dual-layer (AlTiN/AlCrN) coated tool than monolayer AlTiN and AlCrN coated tools. Micromechanical properties influence the wear mechanisms in thermally activated and abrasion dominant crater zones. Dual-layer coated tools reduced the flank wear at the corner radius and crater wear by 35–50% and 40%, respectively. Dynamic wear and abrasion-dissolution wear mechanisms have been explored over the tool rake face. Dual-layer coatings have improved wear performance by diminishing delamination, micro-fracturing of WC grains, binder dissolution and fractured interface boundaries.